From statistical data to spatial knowledge: Informing decision-making in Vietnam - Epprecht, Michael; Heinimann, Andreas; Minot, Nicholas; Müller, Daniel; Robinson, Tim (SAGE Publications, 2007)
Vietnam has developed rapidly over the past 15 years. However, progress was not uniformly distributed across the country. Availability, adequate visualization and analysis of spatially explicit data on socio-economic and environmental aspects can support both research and policy towards sustainable development. Applying appropriate mapping techniques allows gleaning important information from tabular socio-economic data. Spatial analysis of socio-economic phenomena can yield insights into locally-specific patterns and processes that cannot be generated by non-spatial applications. This paper presents techniques and applications that develop and analyze spatially highly disaggregated socioeconomic datasets. A number of examples show how such information can support informed decision-making and research in Vietnam.